The relationship between cancer and medication exposures in systemic lupus erythaematosus: a case–cohort study. Issue 1 (1st June 2007) - Bernatsky, S; Joseph, L; Boivin, J-F; Gordon, C; Urowitz, M; Gladman, D; Fortin, P R; Ginzler, E; Bae, S-C; Barr, S; Edworthy, S; Isenberg, D; et al.
Abstract : Objective: To examine if, in systemic lupus erythaematosus (SLE), exposure to immunosuppressive therapy (cyclophosphamide, azathioprine, methotrexate) increases cancer risk. Methods: A case–cohort study was performed within a multi-site international SLE cohort; subjects were linked to regional tumour registries to determine cancer cases occurring after entry into the cohort. We calculated the hazard ratio (HR) for cancer after exposure to an immunosuppressive drug, in models that controlled for other medications (anti-malarial drugs, systemic glucocorticoids, non-steroidal anti-inflammatory drugs (NSAIDs), aspirin), smoking, age, sex, race/ethnicity, geographic location, calendar year, SLE duration, and lupus damage scores. In the primary analyses, exposures were treated categorically (ever/never) and as time-dependent. Results: Results are presented from 246 cancer cases and 538 controls without cancer. The adjusted HR for overall cancer risk after any immunosuppressive drug was 0.82 (95% CI 0.50–1.36). Age ⩾65, and the presence of non-malignancy damage were associated with overall cancer risk. For lung cancer (n = 35 cases), smoking was also a prominent risk factor. When looking at haematological cancers specifically (n = 46 cases), there was a suggestion of an increased risk after immunosuppressive drug exposures, particularly when these were lagged by a period of 5 years (adjusted HR 2.29, 95% CI 1.02–5.15). Conclusions: In our SLE sample, age ⩾65, damage, and tobacco exposure were associated with cancer risk. Though immunosuppressive therapy may not be the principal driving factor for overall cancer risk, it may contribute to an increased risk of haematological malignancies. Future studies are in progress to evaluate independent influence of medication exposures and disease activity on risk of malignancy.